A model for falling‐tone chorus. Issue 6 (24th March 2014) - Soto‐Chavez, A. R.; Wang, G.; Bhattacharjee, A.; Fu, G. Y.; Smith, H. M.
<x xml:space="preserve">Abstract</x> Motivated by the fact that geomagnetic field inhomogeneity is weak close to the chorus generation region and the observational evidence that falling‐tone chorus tend to have large oblique angles of propagation, we propose that falling‐tone chorus start as a marginally unstable mode. The marginally unstable mode requires the presence of a relatively large damping, which has its origins in the Landau damping of oblique waves in this collisionless environment. A marginally unstable mode produces phase‐space structures that release energy and produce wave chirping. We show that the present model produces results in reasonable agreement with observations.